IMMATURE LOW-DENSITY NEUTROPHILS AS MEDIATORS OF PYODERMA GANGRENOSUM AND INFLAMMATORY BOWEL DISEASE PATHOGENESIS. (21st January 2021) - Jatana, Samreen; Rebert, Nancy; Fernandez, Anthony; Achkar, Jean-Paul; McDonald, Christine
Abstract: Pyoderma gangrenosum (PG) is a debilitating skin condition characterized by deep, pus-filled, non-healing ulcers packed with neutrophils and is a common extraintestinal manifestation of inflammatory bowel disease (IBD). Strikingly, ~40% of people with an initial presentation of PG go on to be also diagnosed with IBD, suggesting that both diseases have common factors driving their pathogenesis. The molecular and cellular mechanisms of PG and IBD co-development are currently unknown, hampering the development of effective treatment strategies for individuals affected by both diseases. Prior studies of individuals with PG demonstrate an enrichment of circulating immature low-density neutrophils (LDGs) that are sensitized to undergo NETosis, a specialized form of cell death. NETosis induces inflammation and, when dysregulated, can promote chronic cycles of inflammation. We hypothesize that LDGs mediate NETosis-driven inflammation in both PG and IBD, but the LDGs from individuals that develop both diseases are functionally distinct. In this translational study, blood samples are collected from healthy subjects or individuals with only PG, only Crohn's disease, only ulcerative colitis, or individuals with both PG and IBD for the analysis of neutrophil populations, neutrophil function, as well as circulating markers of inflammation and NETosis. Preliminary data from 45 subjects demonstrate an enrichment of circulatory LDGs (CD45+ CD15+ CD66b+ CD10+ CD16+ cells from the low density fraction) in individuals with inflammatory disease as compared to healthy subjects (19.2% +/- 2.81%, n=41 vs. 9.9% +/- 2.9%, n=4; p=0.04). This is correlated with increased NETosis in vitro, however differences in the responsiveness of LDGs to priming signals, such as IL-1β, TNFα, and IL-6, are emerging between disease sub-groups. There is considerable variation in the levels of LDGs within disease sub-groups and analyses are underway to determine whether this variation correlates with subject reported disease activity, inflammatory markers (serum C-reactive protein), or circulating markers of NETosis (serum citrullinated histone 3). These preliminary findings point to the presence of a unique population of cells potentially contributing to inflammatory cross-talk between the skin and gut. Further analysis of these potentially disease driving cells may result in more effective care of IBD patients with extraintestinal manifestations, such as PG, through more mechanistically targeted therapeutic approaches, as well as potential biomarker discovery that predicts which PG patients are more likely to develop IBD leading to earlier intervention and better disease outcomes.